Inflation Adjustment and Labour Market Structures : Evidence from a Multi-Country Study - Luca Nunziata; Christopher Bowdler (Institute for the Study of Labor (IZA), 2005)
An empirical analysis of the impact of labour market structures on the response of inflation to macroeconomic shocks is presented. Results based on a 20 country panel show that if labour market coordination is high, the effect on inflation of movements in unemployment, import prices, tax rates and productivity is dampened, both on impact and dynamically. In contrast, monopoly power in labour supply, measured by the percentage unionisation of the workforce, appears to amplify the response of inflation to its reduced form determinants. These findings are attributed to the behaviour of wages following movements in demand- and supply-side conditions.
Keywords: J51; E31; 330; inflation; input price shocks; labour market coordination; trade union density; Inflation; Makroökonomischer Einfluss; Schock; Arbeitsmarktflexibilisierung; Gewerkschaftlicher Organisationsgrad; Schätzung; OECD-Staaten